Modernisasi Sistem Pendidikan Pondok Pesantren Al-Qomar Mempawah Kalimantan Barat - Anwar, Ismail; M. Hambali (Berkala Ilmiah Pendidikan, 2024)
The dynamics of progress, requires Islamic educational institutions including Islamic Boarding Schools to carry out modernization. Thus, Islamic Boarding Schools can be part of the variables and instruments of change as well as icons of progress, in accordance with the development of the times and the demands of reality. The purpose of this study is to conduct an in-depth analysis of matters relating to (1) How is the Implementation of Education at the Al-Qomar Islamic Boarding School in Mempawah, West Kalimantan, (2) What are the forms of modernization of the Al-Qomar Islamic Boarding School in Mempawah, West Kalimantan, (3) What is the impact of modernization of the education system of the Al-Qomar Islamic Boarding School in Mempawah, West Kalimantan. The type of research used is qualitative research with a managerial approach. In this study, data collection was carried out through interviews with several informants, direct observation, or by collecting data and documents needed according to the needs of this study. Furthermore, after the data was collected, the researcher reduced the data, namely by simplifying, concentrating, creating focus, so that final conclusions could be drawn. Furthermore, the results of the study were described in words. The results of this study indicate that the Modernization of the Education System of the Al-Qomar Islamic Boarding School in Mempawah, West Kalimantan: First, the Implementation of Education at the Al-Qomar Islamic Boarding School in Mempawah, West Kalimantan has implemented a modern education system by presenting various types of education in it, such as educational institutions (a) Al-Qomar Islamic High School (b) Al-Qomar Junior High School (c) Al-Qomar Elementary School (d) Al-Qomar Islamic Diniyah School (e) Al-Qomar Al-Qur'an School, and is supported by qualified human resources with many ustads who have graduated from S2 and even the supervisors themselves have graduated from S3, and the implementation of an adaptive curriculum that is adjusted to the needs of the market share, as well as continuing to improve educational facilities and infrastructure. The second form of modernization of the education system of the Al-Qomar Islamic boarding school in Mempawah, West Kalimantan is carried out with (1) Physical modernization, meaning continuing to strive to build representative educational infrastructure in accordance with the demands of educational standards (2) Non-physical modernization. This means continuing to strive to renew institutions, curriculum, teaching methods, and learning evaluations. Third, the impact of the modernization of the education system of the Al-Qomar Islamic boarding school in Mempawah, West Kalimantan can increase public trust in the form of the large number of children from the community who have been entrusted to the Al-Qomar Islamic boarding school.